Aspectual features and categorial shift: deverbal nominals in German and English. (May 2019) - Demske, Ulrike
Abstract: The point of departure of this paper is the claim by Heyvaert, Maekelberghe & Buyle (2019) that the suffix - ing has no aspectual meaning in English gerunds. Rather, the interpretation of nominal and verbal gerunds depends, so they argue, on situation or viewpoint aspect, a claim that contradicts the wide-spread view that the aspectual meaning of English gerunds is brought about by the nominalizing suffix. The present paper addresses the issue from a comparative perspective, focusing on German ung -nominals: while they share aspectual features with their English counterparts, empirical evidence from productivity, distribution, and argument linking shows (i) that the derivational suffix - ung imposes aspectual restrictions on possible verb bases, and (ii) that with respect to argument linking, the deverbal nominal favors the state component of a complex event predicate over its process component. From the historical record of German, we learn that these aspectual restrictions do not hold for ung -nominals in earlier periods of German. With the rise of aspectual restrictions, the nominalization pattern turns more nominal resulting in a position further towards the nominal end of the deverbalization continuum. It appears, then, that it is only in the historical pariods of German that ung -nominals pattern with English nominals as regards their aspectual features. Currently, German ung -nominals are more noun-like than nominal (and verbal) gerunds in English. Highlights: Aspectual meaning of ung -nominals provided by Aktionsart of the verb and context in Present-day and Early New High German. Data from Present-day German and Early New High German witness a categorial shift of ung -nominals in the recent history of German. Aspectual properties of nominalizations in English and German suggest different positions on deverbalization continuum.